ANALYSIS OF LANGUAGE ERRORS AT THE PHONOLOGY AND MORPHOLOGY LEVEL ON THE PRIANGAN NEWS SITE LIFESTYLE CATEGORY, AUGUST 2023 EDITION - Aldhanisa Nursafitri; Amelia Nurfitri Annisa; Adinda Dewi Lestari; Neng Sri Wahyuni N.B; Ai Siti Nurjamilah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Language is an important aspect in communication activities. When communicating, the language used is not only spoken, but can also be written. When writing, whether writing for official activities, such as in teaching and learning activities at school or for informal activities, it is not uncommon for us to encounter language errors. These errors occur due to the writer's limited mastery of language and mistakes in writing a word or sentence. This research aims to correct errors in punctuation, letter writing, the affixation process, as well as to find out the results of analysis regarding forms of language errors at the phonological and morphological levels on the August 2023 edition of the Kabar Priangan Tasikmalaya news site. The research method used is a qualitative descriptive method. The results of this research show that of the 4 news texts, there were 20 errors, including: 14 or 70% errors at the phonological level and 6 or 30% errors at the morphological level.